Functional specialization of Nicotiana attenuata phytochromes in leaf development and flowering time. Issue 3 (March 2017) - Fragoso, Variluska; Oh, Youngjoo; Kim, Sang‐Gyu; Gase, Klaus; Baldwin, Ian Thomas
Abstract: Phytochromes mainly function in photoautotrophic organisms to adjust growth in response to fluctuating light signals. The different isoforms of plant phytochromes often display both conserved and divergent roles, presumably to fine‐tune plant responses to environmental signals and optimize fitness. Here we describe the distinct, yet partially redundant, roles of phytochromes NaPHYA, NaPHYB1 and NaPHYB2 in a wild tobacco species, Nicotiana attenuata using RNAi‐silenced phytochrome lines. Consistent with results reported from other species, silencing the expression of NaPHYA or NaPHYB2 in N. attenuata had mild or no influence on plant development as long as NaPHYB1 was functional; whereas silencing the expression of NaPHYB1 alone strongly altered flowering time and leaf morphology. The contribution of NaPHYB2 became significant only in the absence of NaPHYB1 ; plants silenced for both NaPHYB1 and NaPHYB2 largely skipped the rosette‐stage of growth to rapidly produce long, slender stalks that bore flowers early: hallmarks of the shade‐avoidance responses. The phenotyping of phytochrome‐silenced lines, combined with sequence and transcript accumulation analysis, suggest the independent functional diversification of the phytochromes, and a dominant role of NaPHYB1 and NaPHYB2 in N. attenuata's vegetative and reproductive development. Abstract : To understand how a wild tobacco species perceives light, we examined transgenic plants impaired in their ability to "see" particular wavelengths of light by silencing the expression of photoreceptor proteins, the phytochromes. The phytochromes were specialized in their function: B1 controlled leaf development while B2 controlled flower development.